The natural history of type 2 endoleaks after endovascular aneurysm repair justifies conservative management. (October 2018) - Ajalat, Mark; Williams, Russell; Wilson, Samuel E
Objective: Management of type 2 endoleaks after endovascular aneurysm repair has been controversial. Some advocate for conservative management, while others believe that intervention is indicated. This study investigated the natural history of type 2 endoleaks in order to derive direction in management. Methods: Patients who had endovascular aneurysm repair at the Veterans Affairs Long Beach were retrospectively identified and computerized tomographic angiography was independently reviewed by a radiologist and a vascular surgeon. Type 2 endoleaks were analyzed for the following outcomes: rupture, duration of endoleak, spontaneous resolution, changes in the size of the aneurysm sac, and reintervention rates. Results: Of the 160 patients who had completed required follow-up to date (mean 3 years) after endovascular aneurysm repair, 39 (24.4%) patients were identified as having a type 2 endoleak on computerized tomographic angiography imaging. 6 (15.4%) of these 39 patients required repair due to aneurysm sac growth >1 cm. 2 (5.13%) were repaired with an open procedure and 4 (10.3%) with an endovascular approach. Of these 6 aneurysm leaks requiring repair, 4 (66.7%) had a simultaneous endoleak (types 1 or 3) in addition to the identified type 2 endoleak. Spontaneous resolution of type 2 endoleaks occurred in 16 (41.0%) patients. 4 patients (10.3%) had delayed type 2 endoleaks that presented 4, 9, 12, and 23 months after their 30 day post op computed tomography was normal. None of the 4 patients with delayed type 2 endoleaks required reintervention and none had aneurysm sac growth greater than 5 mm. Conclusions: Overall, we found that 85% of patients who had type 2 endoleaks did not require intervention after a mean follow-up time of 3 years. The association of a type 1 or 3 endoleak with a type 2 endoleak was more likely to require correction due to aneurysm expansion >1 cm, thus type 2 endoleaks associated with another type of endoleak require more aggressive management.